2022
DOI: 10.1038/s41598-022-15769-4
|View full text |Cite
|
Sign up to set email alerts
|

A continuous time meta-analysis of the relationship between conspiracy beliefs and individual preventive behavior during the COVID-19 pandemic

Abstract: In several longitudinal studies, reduced willingness to show COVID-19-related preventive behavior (e.g., wearing masks, social distancing) has been partially attributed to misinformation and conspiracy beliefs. However, there is considerable uncertainty with respect to the strength of the relationship and whether the negative relationship exists in both directions (reciprocal effects). One explanation of the heterogeneity pertains to the fact that the time interval between consecutive measurement occasions var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In addition, it is worth considering that the strength of the relationship between the examined personality constructs and conspiracy mentality may increase both for the aggregate scores and the network analysis if there is a considerable time lag between assessing conspiracy beliefs and their correlates. Such a tendency was identified in a meta-analysis examining the relationship between conspiracy beliefs and COVID-19-related preventive behavior (Stasielowicz, 2022a). Specifically, the strongest relationship was estimated for time lags of three to six months.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, it is worth considering that the strength of the relationship between the examined personality constructs and conspiracy mentality may increase both for the aggregate scores and the network analysis if there is a considerable time lag between assessing conspiracy beliefs and their correlates. Such a tendency was identified in a meta-analysis examining the relationship between conspiracy beliefs and COVID-19-related preventive behavior (Stasielowicz, 2022a). Specifically, the strongest relationship was estimated for time lags of three to six months.…”
Section: Discussionmentioning
confidence: 93%
“…It is plausible that personality acts both as a cause and an outcome. To examine whether reciprocal effects exist between personality and conspiracy mentality, one could conduct longitudinal studies and account for variables identified as relevant predictors of conspiracy beliefs in previous studies (Hornsey et al, 2022;Stasielowicz, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…Conspiracy theories are defined as causal theories that attribute events to the intentional activities of certain groups 130 . Evidence showed that belief in conspiracy theories is negatively associated with compliance to governmental rules during the pandemic [131][132][133] and the intentions to get the anti-COVID-19 vaccine [134][135][136][137] .…”
Section: Spiritual Supportmentioning
confidence: 99%
“…Although social networking sites were initially created to facilitate interpersonal communication and social interactions between users, these platforms have also become one of the main facilitators of misinformation 1 4 . Unfortunately, as countless studies and reports have documented, misinformation can have dire consequences for the political and social wellbeing of societies around the globe 5 8 . While researchers studying misinformation have made insightful contributions to our understanding of who is most susceptible to misinformation 9 11 , seminal papers have made conclusions about what makes people susceptible by studying misinformation mostly in a social vacuum, when in reality, individuals often consume news in social settings.…”
Section: Introductionmentioning
confidence: 99%